A novel assessment of potentially toxic elements (PTEs) in water and sediment samples from the indus river, Pakistan: An ecological risk assessment approach (2024)
Pakistan, a country with limited water resources and highly vulnerable to the adverse effects of climate change, faces numerous challenges in managing its water supply. In this sense, this study assessed potentially toxic elements (PTEs) in the surface water and sediments of Pakistan’s Indus River and its tributaries. Key water quality parameters such as pH, electrical conductivity (EC), and total dissolved solids (TDS) were determined, with respective average values of 7.1, 40 μS/cm, and 208 mg L− 1. The concentrations of Cd, Cr, Cu, Ni, and Zn in surface water samples averaged 26 μg L− 1, 0.9 μg L− 1, 1.4 μg L− 1, 22 μg L− 1, and 2.1 μg L− 1, respectively. The general sediment PTE profile was Ni > Cd > Zn > Cu > Cr. Certain PTE levels exceeded recommended thresholds, indicating the establishment of environmental pollution. Calculated geo-accumulation index values suggested moderate to heavy pollution levels in sediment, with PERI (404) values reinforcing the ecological risk posed by elevated PTE concentrations. Furthermore, significant correlations were observed between specific PTE pairs in both water and sediment samples. This study contributes with novel insights into the distribution and ecological implications of PTE contamination in the Indus River and its tributaries, paving the way for ecological risk management efforts.